Age-related macular degeneration associated with optic disc drusen - Anas Alkhabaz; Min Young Kim; Min Young Kim; Rishita Pujari; Jamie Zhang; Yulan Ren; Loh-Shan Bryan Leung; Yaping Joyce Liao (Frontiers in Ophthalmology)
ObjectiveThe aim of this study was to investigate the risk of age-related macular degeneration (AMD) in association with optic disc drusen (ODD).DesignThis was an observational, cross-sectional study.ParticipantsParticipants were consecutive patients with and without ODD from the neuro-ophthalmology clinic. Ten patients with concomitant ODD-AMD were sub-analyzed.MethodsThe two cohorts were identified from a prospectively recruited dataset between July 2022 and June 2024. Patients received formal diagnoses of ODD and AMD after ophthalmic and imaging assessment. A logistic regression model was utilized in calculating AMD risk to account for demographic differences.ResultsA total of 94 patients with ODD (median age: 44 [Q1: 20, Q3: 69], 64% women) and 100 patients without ODD (median age: 60 [Q1: 44, Q3: 69], 48% women) were identified. AMD was observed in 9.6% and 3% of the ODD and non-ODD cohorts, respectively. The risk of AMD was higher in the ODD group (OR = 3.93, 95% CI: 0.89–21.85, p = 0.084). Although the association was not statistically significant, a logistic regression model attributed that to the age difference between the two cohorts. Of the 10 patients with ODD-AMD, 70% had a family history of AMD. These patients were all Caucasians and had a median age of 75 years (range: 56–91); 70% were women. Only 30% were smokers. On optic disc imaging, 70% of eyes demonstrated moderate-to-severe ODD.ConclusionPatients with ODD might be at a higher risk of AMD compared to patients without ODD, and AMD screening might be warranted. A family history of AMD is often present, indicating shared genetic risk factors.